Optimization of fermentation conditions for acidic Monacolin K production by Monascus purpureus with response surface method - CHEN Yang, HONG Housheng (Zhongguo niangzao)
Acidic Monacolin K is a physiologically active substance with multiple functions such as lipid-lowering, anti-fatigue, anti-microbial, anti-tumor and neuroprotective, and is considered to be a good hypolipidemic drug. In order to increase the content of Monacolin K in Monascus fermentation products, using Monascus purpureus as the fermentation strain, the solid-state fermentation conditions of M. purpureus were optimized by single factor test and response surface method. The results showed that the optimal fermentation conditions for acidic Monacolin K production were as follow: solid-liquid ratio 1∶5 (g∶ml), contents of glycerin, soybean powder, L-arginine, sodium acetate 2.34%, 1.97%, 0.60%, 0.15%, respectively. The culture was taken at 30 ℃ at normal temperature for 3 d at the beginning of the experiment, and the low temperature culture was taken at 20 ℃ for 21 d at the end of the experiment, with the total fermentation time was 24 d. On the 3rd and 4th day of low-temperature fermentation, L-arginine 0.60% and sodium acetate 0.15% were added. Under the optimized conditions, the yield of acidic Monacolin K could reach 7.59 mg/g, which was 153.85% higher than that before optimization.